Building proxies that capture time-variation in expected returns using a VAR approach - Sousa, Ricardo M. (2011)
I use the consumer's budget constraint to derive a relationship between stock market returns, the residuals of the trend relationship among consumption, aggregate wealth, and labour income, and three major sources of risk: future changes in the housing consumption share, future labour income growth, and future consumption growth. I model the joint dynamics of changes in the housing consumption share, consumption growth, wealth growth, income growth, asset returns, consumptionwealth ratio and dividend-price ratio, and show that asset returns largely reflect expectations about long-run risk. On the other hand, unexpected shocks play a negligible role in the context of forecasting future asset returns. Combining the intertemporal budget constraint and the forecasting properties of an informative Vector-Autogression (VAR), one can, therefore, generate the predictability of many economically motivated variables developed in the literature on asset pricing, and accommodate the implications of a wide class of optimal models of consumer behaviour without imposing a functional form on preferences.